Efficacy of a reduced-dosage PRRS MLV vaccine against a NADC34-like strain of porcine reproductive and respiratory syndrome virus - Yan, Xinyu; Liu, Jiayu; Yue, Fengxiong; Lin, Yan; Li, Yan; Wu, Wensi; Zhao, Shan; Huang, Xiaobo; Zhao, Qin; Wen, Yiping; Cao, Sanjie; Du, Senyan; et al. (Frontiers in Veterinary Science, 2025)
IntroductionAfter being discovered for the first time in China in 2017, porcine reproductive and respiratory syndrome virus (PRRSV) NADC34-like strains have become the prevalent strain of PRRSV in certain regions of China. Our previous study showed that reduced Ingelvac PRRS MLV vaccination dosages against NADC30-like CF PRRSV had a better protection effect than the normal dosage. However, the protective effect of reduced dosages vaccination of Ingelvac PRRS MLV against NADC34-like PRRSV is unclear. Therefore, this study compared the effectiveness of 0.1 and 1 dosages against a NADC34-like PRRSV infection using commercial PRRSV vaccines, Ingelvac PRRS MLV, which have been widely utilized in China.MethodsIn this study, we immunized piglets with two different dosages of the MLV vaccine and infected piglets within a nasal way with NADC34-like CF PRRSV at 42 days post-vaccination. We observed the changes in growth performance before and after the NADC34-like PRRSV DX strain challenge and the protective effect of different vaccine dosages through multiple assays.ResultsAfter the challenge, the piglets from the challenge control group displayed clinical signs typical of PRRSV infection, including transient fever, high viremia, mild clinical symptoms, and histopathological changes in the lungs and lymph nodes, which indicates DX is a virulent virus. Without the challenge, the average daily gain of the non-immunized group at 5 weeks after the vaccination is greater than that of the 0.01 dosage group than that of the 1 dosage group, which proved that the commercial MLV vaccine has a negative effect on the growth performance of pigs and this effect may be dose-dependent. After the NADC34-like PRRSV challenge, there was no difference in average daily gain between the immunized pigs and pigs from the challenge control group. From the perspective of clinical score, gross lung lesions, and microscopic lesions, immunization with MLV vaccine can indeed relieve symptoms and lesions caused by the virus, and 0.1 dosage vaccination has a better effect in these aspects. Also, both dosages of MLV immunization shortened viremia with similar effects.DiscussionOur research suggests that the MLV vaccine can provide piglets with some protection against NADC34-like PRRSV and the 0.1 dosage Ingelvac PRRS MLV vaccination showed greater benefits in our study. Therefore, considering the cost, side effects, and subsequent protective effects, we can adjust the immune dosage appropriately after further investigation to ensure safety, improve production efficiency, and reduce immunization costs.